2022
DOI: 10.1021/acs.macromol.2c01531
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding-Induced Clusteroluminescence and UCST-Type Thermoresponsiveness of Nonconjugated Copolymers

Abstract: Stimuli-responsive light-emitting polymers (SRLEPs) have many promising applications. However, the synthesis of SRLEPs from nonconjugated and water-soluble monomers remains a challenge. Herein, for the first time, nonconjugated luminescent polymers with an upper critical solution temperature (UCST) in aqueous solution are reported. The polymer is synthesized through copolymerization of a strong hydrogen-donating monomer, acrylic acid (AAc), and a strong hydrogen-accepting monomer, N-vinylcaprolactam (NVCL). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…35,36 In the past few years, numerous polymers without conventional chromophores have been observed to exhibit significant intrinsic photoluminescence (PL) in the aggregate or solid state. 37–57 Tang et al have termed this fluorescence phenomenon as clusterization-triggered emission. 58,59 The emission is described as clusteroluminescence and the chromophores responsible for it are classified as clusteroluminogens.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 In the past few years, numerous polymers without conventional chromophores have been observed to exhibit significant intrinsic photoluminescence (PL) in the aggregate or solid state. 37–57 Tang et al have termed this fluorescence phenomenon as clusterization-triggered emission. 58,59 The emission is described as clusteroluminescence and the chromophores responsible for it are classified as clusteroluminogens.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to DHCs, both of the carbonyl absorption peaks of AA and NIPAM were found, indicating the successful copolymerization of AA and NIPAM. In particular, the carbonyl absorption band of NIPAM gradually shifted toward the lower wave number direction (from 1654 cm −1 to 1643 cm −1 ), which is a result of the restricted stretching vibration due to PAA and PNIPAM hydrogen‐bonding formation [16b,19] . on the other hand, the effect of urea on the fluorescence properties was studied.…”
Section: Resultsmentioning
confidence: 99%
“…As the solvent isotope can induce the formation of different types of LCST/UCST behaviors, it is more desirable to develop other alternative approaches to revealing solvation status and hydrogen bondings of subunits in a common solvent. The emergence of nontraditional intrinsic luminescence (NTIL) may hold great promise in addressing the challenge. Different from traditional fluorescence analysis using a conjugated fluorescence moiety to determine the critical aggregation temperature by monitoring variations of the hydrophobic/hydrophilic microenvironment, the clustering of nonconventional chromophores with lone pairs (n) and/or π electrons is liable to extend electron delocalization and rigidify conformations via through-space electronic communications. Consequently, NTIL-type polymers can exhibit remarkable emissions as monitored by fluorometry.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the amide group has been recognized as a promising luminogen in polyamides, , polyacrylamides, and polymethacrylamides with NTIL features. The origin of the fluorescence can be ascribed to amide-related hydrogen bonding interactions, by which chain conformations are rigidified, and aggregation or clustering of heteroatoms and carbonyl groups is beneficial for enhancing fluorescence emissions. Thus far, LCST-type PNIPAM, poly­( N -vinylcaprolactam), and hyperbranched poly­(ether amide) as well as the UCST-type copolymer comprising acrylic acid and N -vinylcaprolactam units with NTIL features have been documented, and thermoresponsive behaviors can be revealed by monitoring temperature-dependent fluorescence intensity. For instance, Jiang et al have reported on LCST-dependent fluorescence behavior of thermoresponsive branched poly­(ether amide)­s, in which the critical aggregation temperature determined by the plots of fluorescence intensity and temperature is close to the LCST value given by turbidimetry .…”
Section: Introductionmentioning
confidence: 99%